Elevated levels of Wnt signaling disrupt thymus morphogenesis and function - Jeremy B. Swann (Nature Portfolio, 2017)
Abstract All vertebrates possess a thymus, whose epithelial microenvironment is essential for T cell development and maturation. Despite the importance of the thymus for cellular immune defense, many questions surrounding its morphogenesis remain unanswered. Here, we demonstrate that, in contrast to the situation in many other epithelial cell types, differentiation of thymic epithelial cells (TECs) proceeds normally in the absence of canonical Wnt signaling and the classical adhesion molecule E-cadherin. By contrast, TEC-intrinsic activation of β-catenin-dependent Wnt signaling blocks the morphogenesis of the thymus, and overexpression of a secreted Wnt ligand by TECs dominantly modifies the morphogenesis not only of the thymus, but also of the parathyroid and thyroid. These observations indicate that Wnt signaling activity in the thymus needs to be precisely controlled to support normal TEC differentiation, and suggest possible mechanisms underlying anatomical variations of the thymus, parathyroid and thyroid in humans.